Enhancing Traffic Operations and Safety Performance at Roundabout Intersections: A Simulation-Based Case Study of Dhalkebar Roundabout on the East-West Highway - Kunwar, Deepak Bahadur; Pradhananga, Rojee; Parajuli, Sujan; Shrestha, Saurav (Journal on Transportation System and Engineering, 2025)
The main aim of this study is to explore alternatives to enhance the traffic operational and safety performance of the Dhalkebar three-legged roundabout in terms of capacity, delay, operational speed, LoS, and traffic conflicts using VISSIM microsimulation model and Surrogate Safety Assessment Model (SSAM) software under three improvement alternatives viz; with geometric improvement, metering concept, and turbo roundabout. The evaluation of the alternatives has been conducted for both base-year traffic and forecasted (in next 10 year) traffic scenarios. For the base-year traffic scenario, it was found that alternative III performed the best, with reductions in delay, traffic conflicts, and improvements in capacity by 34.55 seconds, 1044 conflicts, and 604 PCU/hr, respectively. Additionally, the LoS improved to level B, and the average operational speed was higher compared to the other two alternatives. Similarly, for the forecasted traffic scenario, alternative III again showed the best performance, with reductions in delay and conflict, along with an increase in capacity by 44.58 seconds, 5776 conflicts, and 1074 PCU/hr, respectively. The LoS improved to level C, and the average operational speed was higher than the other alternatives. Therefore, in terms of both safety and traffic operational performance, alternative III was identified as the best improvement option for both the base and forecasted traffic scenarios.